"I suddenly felt I'd aged": A qualitative study of patient experiences of polymyalgia rheumatica (PMR). Issue 5 (May 2015) - Twohig, Helen; Mitchell, Caroline; Mallen, Christian; Adebajo, Adewale; Mathers, Nigel
Highlights The 5 main themes were: pain, stiffness and weakness, disability, treatment and disease course, experience of care and psychological impact. Some aspects of patients' experiences challenge conventional understanding of PMR. A conceptual framework was developed from the interlinked themes and subthemes which will be used to develop a patient reported outcome measure for PMR.